Treatment of Frontal Sinus Osteomyelitis in the Age of Endoscopy. Issue 3 (May 2021) - Thompson, Harrison M.; Tilak, Ashwini M.; Miller, Peter L.; Grayson, Jessica W.; Cho, Do-Yeon; Woodworth, Bradford A.
Objective: Frontal sinus osteomyelitis is a severe complication which can result from chronic rhinosinusitis, trauma, or as a complication of reconstruction or obliteration of the frontal sinus. The objective of the current study is to evaluate the contemporary management of frontal sinus osteomyelitis in light of recent advancements in endoscopic surgical techniques. Methods: Review of a prospectively collected database of patients with frontal sinus pathology was performed from 2008–2020. Data from individuals with frontal sinus osteomyelitis was collected including demographics, etiology, surgical technique, adjunctive medical treatments, complications, and clinical follow up. Results: Sixteen patients (average age 48.3, range 8–84) were included in the study. An open approach was utilized in 6 patients (2 osteoplastic flaps, 3 Reidel procedures, 1 cranialization). Seven patients underwent completely endoscopic approaches (3 Draf IIB, 4 Draf III), while 3 individuals had combined procedures (Lynch with Draf III, osteoplastic flap + Draf III, fistula excision + Draf IIb). All patients received 6 weeks of antibiotics. Average clinical follow up was 24.4 months with no patients requiring revision procedures. Conclusion: Endoscopic, endoscopic-assisted, and open approaches were utilized successfully in the current series of patients with osteomyelitis of the anterior table of the frontal sinus. While the progression of endoscopic techniques allows an additional surgical treatment option, it is important to select patients appropriately as open procedures continue to have an important role in the treatment algorithm.